Consumer intention to consume luxury fashion among generation Y in Johor Bahru [electronic resource] - Munirah Mohamad Rifin 1993- author 639035 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Pengurusan (Pemasaran)) - Universiti Teknologi Malaysia, 2016